2022
DOI: 10.1111/1365-2478.13289
|View full text |Cite
|
Sign up to set email alerts
|

Structural information derived from ambient noise tomography over a hydrocarbon‐producing region in the Cachar fold belt, lower Assam, northeast India

Abstract: Ambient noise tomography is a powerful tool that has found increasing application in reservoir analysis and imaging. The Cachar fold belt in lower Assam, northeast India encompasses several wells under active hydrocarbon production, along with several dry wells. To overcome the lack of active seismic data over the entire fold belt, a passive seismic study was carried out to image the concealed three-dimensional sub-surface structures. The data were recorded from February to November 2011 by a network of 65 wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…4b) reveals variation in the subsurface topography that correlates well with the gentle surface topography of the Cachar fold belt. Ambient noise tomography (Shekar et al, 2023) using the current seismic network also revealed near surface (≤ 2km) structures beneath the Cachar fold belt that correlate with the observed subsurface deformation pattern. The geometry of the Balakandi and Silchar synclines and the Ramphan anticline are well delineated beneath the pro le A-A'.…”
Section: Vertical Sectionsmentioning
confidence: 56%
“…4b) reveals variation in the subsurface topography that correlates well with the gentle surface topography of the Cachar fold belt. Ambient noise tomography (Shekar et al, 2023) using the current seismic network also revealed near surface (≤ 2km) structures beneath the Cachar fold belt that correlate with the observed subsurface deformation pattern. The geometry of the Balakandi and Silchar synclines and the Ramphan anticline are well delineated beneath the pro le A-A'.…”
Section: Vertical Sectionsmentioning
confidence: 56%
“…Surface wave group velocity maps produced by ray-based methods (e.g. Shekar et al 2022) can be used to characterize Earth structure in our source inversion scheme. More generally, such maps can be used as starting structure models in a future joint source-structure acoustic inversion scheme, which may serve to refine traditional ambient noise tomographic models.…”
Section: Discussionmentioning
confidence: 99%
“…Surface wave group velocity maps produced by ray-based methods (e.g. Shekar et al 2023) can be used to characterize Earth structure in our source inversion scheme. More generally, such maps can be used as starting structure models in a future joint source-structure acoustic inversion scheme, which may serve to refine traditional ambient noise tomographic models.…”
Section: Discussionmentioning
confidence: 99%